The Effect of Heimlich Maneuver Education Using Audiovisual Media on Improving Mothers’ Knowledge of Choking Management in Children at RA-Al Hikmah Parongpong in 2026 - Lisbet Octovia Manalu; Dela Savira; Arieni Ramadhan (Health Dynamics, 2026)
Background: Choking is a common condition in children and can be fatal if not treated quickly and appropriately. Mothers’ lack of knowledge about choking management increases the risk of complications and death, so education, especially about the Heimlich maneuver, is needed to increase knowledge and prevent child mortality. Objective: To determine the effect of audiovisual education on the Heimlich maneuver on mothers’ knowledge of choking management in children at RA Al-Hikmah. Methods: This was a quantitative study with a pre-experimental one-group pre-test–post-test design. The sample consisted of 45 respondents, using a total sampling approach. A knowledge questionnaire was administered before and after the health education, and the changes were analyzed using the Wilcoxon test. Results: Mothers’ knowledge increased significantly after health education. Before the intervention, most mothers had low knowledge levels, but after education, knowledge levels increased significantly. The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating that health education significantly increased mothers’ knowledge. Conclusion: Audiovisual-based health education on the Heimlich maneuver is effective in improving mothers’ knowledge of choking management in children. This approach can be recommended as an alternative strategy in community-based health education programs to enhance early first aid preparedness.